The Islamic Religious Education Teacher Program on Students’ Mental Health of Elementary School - Wahyu Nur Istiqomah; Agus Ahmad; Edi Suryadi; Siti Roudlatul Jannah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This research explores the impact of the Islamic Education Teacher Education Program on the mental well-being of students at SDN 01 Pendowo Asri, Dente Teladas. Through comprehensive analysis, the research aims to evaluate the extent to which the program contributes to improving students' mental well-being. This research focuses on three main aspects: first, increasing religious knowledge; second, develop an understanding of moral values; and third, students' ability to deal with stress. The findings of this study significantly demonstrate the positive impact of the program on students' mental well-being. The implications of these findings emphasize the important role of Islamic education in supporting and improving students' mental well-being in the school environment, creating a more balanced and supportive atmosphere for student growth and development. The Islamic Education Teacher Education Program can have a significant impact on the mental health of students at SDN 01 Pendowo Asri, Dente Teladas. These impacts include various psychological aspects. Keywords: Mental Health, Islamic Religious Education Teacher